Penyusunan Program Literasi Tematik Sebagai Strategi Pengenalan Keparlemenan Untuk Anak Kelas Tinggi Di Perpustakaan Parlemen - Jelisa, Tirilla; Primadesi, Yona (Scinary, 2025)
This research aims to design a Thematic Literacy Program as a strategy to introduce parliamentary concepts to young children at the Indonesian House of Representatives (DPR RI) Library, addressing the challenges of incidental, unstructured, and non-parliament-specific literacy visit materials. The program seeks to enhance basic literacy while systematically and interactively introducing parliamentary concepts. The Backward Design method was employed, involving: (1) identifying learning outcomes, (2) determining assessment evidence, and (3) designing interactive activities such as storytelling and role-playing. Additionally, the Design Thinking approach was used to develop an educational game, Gigih si Garuda: Adventure in the World of Parliament, through empathize, define, ideate, prototype, and test stages. Results from a limited trial on May 7, 2025, and community testing showed positive responses to the game’s design and mechanics, proving its effectiveness as a national education tool, reinforcing the library’s role as a democratic knowledge hub.